2007
DOI: 10.1016/j.jconrel.2006.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically targeted delivery into endothelial and smooth muscle cells in ex vivo arteries

Abstract: This study tested the hypothesis that ultrasound can target intracellular uptake of drugs into vascular endothelial cells (ECs) at low to intermediate energy and into smooth muscle cells (SMCs) at high energy. Ultrasound-enhanced delivery has been shown to enhance and target intracellular drug and gene delivery in the vasculature to treat cardiovascular disease, but quantitative studies of the delivery process are lacking. Viable ex vivo porcine carotid arteries were placed in a solution containing a model dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Acoustic cavitation is the formation, oscillation and collapse of gas-filled bubbles in a fluid medium exposed to ultrasound (10), thereby enhancing the permeability of cell membranes through the creation of pores (11). Recently, several groups showed that cavitation can also be used for the intracellular delivery of small molecules (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic cavitation is the formation, oscillation and collapse of gas-filled bubbles in a fluid medium exposed to ultrasound (10), thereby enhancing the permeability of cell membranes through the creation of pores (11). Recently, several groups showed that cavitation can also be used for the intracellular delivery of small molecules (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that ultrasound (US) can delivery DNA, proteins, and other formulations of molecules of interest into viable cells [1][2][3][4][5][6][7][8]. It has been hypothesized that US energy, often amplified by microbubble activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compelling results obtained recently have stimulated great interest in the development of sonoporation applications with exciting possibilities [1][2][3][4][5][6][7][8]. However, progress in the field is hindered by a lack of mechanistic understanding of the sonoporation process and its outcome beyond demonstrations of initial feasibility [20].…”
Section: Introductionmentioning
confidence: 99%
“…33 Despite the development of a large number of preclinical delivery systems, very few new technologies or materials have entered clinical trials. One hurdle is that regulatory approval requires well-defined products for clinical use.…”
Section: Ta Et Almentioning
confidence: 99%